Network pharmacology- and molecular docking-based analyses of the antihypertensive mechanism of Ilex kudingcha - Liao, Fei; Yousif, Muhammad; Huang, Ruya; Qiao, Yanlong; Hu, Yanchun (Frontiers in Endocrinology, 2023)
Herein, network pharmacology and molecular docking Abstract: . Through topologicalwas used to identify the active components in Ilex kudingcha and common hypertension-related targets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted, and molecular docking was performed to verify molecular dynamic simulations. Six active components in Ilex kudingcha were identified; furthermore, 123 target genes common to hypertension were identified. Topological analysis, revealed the strongly associated proteins were found, of which, with RELA, AKT1, JUN, TP53, TNF, and MAPK1,were being the predicted targets of the studied traditional Chinese medicine. In addition, GO enrichment results showedanalysis revealed significant enrichment of biological processes, such as oxidative stress, epithelial cell proliferation, cellular response to chemical stress, response to xenobiotic stimulus, and wound healing. Furthermore, KEGG enrichment showedanalysis revealed that the genes were particularly enriched in the Lipidlipid and atherosclerosis, Fluidfluid shear stress and atherosclerosis, and other pathways. Molecular docking results showedrevealed that the key components in Ilex Kudingcha hadkudingcha exhibited good binding potential to bind to the target genes RELA, AKT1, JUN, TP53, TNF, and IL-6. Ilex Kudingcha may playOur study results suggest that Ilex kudingcha plays a role in thehypertension treatment of hypertension by exerting hypolipidemic, anti-inflammation, antioxidation and inhibitioninflammatory, and antioxidant effects and inhibiting the transcription of atherosclerosis gene transcription.-related genes.